Pengaruh Hedonic Motive dan Shopping Lifestyle Terhadap Implusive Buying Pada Meekow Mataram - Nazari, Sulhan; Athar, Handry Sudiartha (Postgraduate, University of Mataram, 2024)
This research aims to determine the influence of hedonic motive and shopping lifestyle on Meekow Mataram. This research was conducted on Meekow in Mataram. This type of research is causal associative research which aims to determine the influence of hedonic motive and shopping lifestyle on impulsive buying. The data collection tool is carried out through distributing questionnaires to consumers who had made impulsive purchases at Meekow Mataram. The sample used was 100 samples using non-probability sampling techniques where samples were taken non-randomly with purposive sampling. The data processing technique uses multiple linear regression analysis methods with the help of the IBM SPSS 22 software application. The results of this study show that the hedonic motive and shopping lifestyle variables have a positive and significant effect on impulsive buying in Meekow Mataram.